Corporate finance with CD - Ross, Stephen A.; Westerfield, Randolph W.; Jaffe, Jeffrey (Boston : McGraw-Hill, 2005)
Business
Keywords: Corporate finance; Financial planning; Capital budgeting; Investment; Capital market; Cash management; Credit management; Financial distress; International corporate finance